PENGARUH KUALITAS LAYANAN INTI DAN KUALITAS LAYANAN PERIPHERAL TERHADAP KEPUASAN NASABAH (Studi Kasus Pada Bank BRI Kantor Kas Unisma) - Olivia Jeymima; M Hufron; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT This research was conducted at Bank BRI Office of Cash Unisma, Malang. This study aims to analyze the effect of core service quality and service quality peripherals to customer satisfaction simultaneously and partially. Independent variables from this research are core service quality and peripheral service quality, and customer satisfaction variable as dependent variable. The sample used is 98 respondents. Data collection method used is questionnaire. The analysis used is Analysis multiple linear by using IBM SPSS Statistic 20. The results showed that the quality of core service and of peripheral service quality simultaneously affect the customer satisfaction of Bank BRI Unisma Cash Office, core service quality and peripheral service quality significantly influence partially to customer satisfaction of Bank BRI Office of Cash UnismaKeyword : Core Service Quality, Peripheral Service Quality, Customer Satisfaction